An integrative model of consumer's intentions to purchase travel online in Sabah : a case study of nature lodge Kinabatangan / Latipah Omar - Omar, Latipah (2014)
The purpose of this project paper is to study the factor influences intention to purchase travel online among local and international tourists in Sabah. The researcher is focusing on the communicability, perceived behavioural control, trust, compatibility, complexity, perceived risk and perceived relative advantage. For the aid of this research, quantitative data collection method and convenience sampling is use in aiding the research. The target population for this study is the local and international tourists that visiting in Sabah specifically in Nature Lodge Kinabatangan Sandakan and Kota Kinabalu. 152 questionnaires distributed to the respondent with balance proportion whereby 76 sets for local tourists and another 76 sets for international tourists. Researcher analysed the data by using Statistical Package for the Social Sciences (SPSS) software.